1991
DOI: 10.1103/physrevlett.67.671
|View full text |Cite
|
Sign up to set email alerts
|

Multifragment emission in reactions induced by 0.90 and 3.6 GeVHe3ions on

Abstract: Multifragment events for intermediate-mass fragments (3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…From the comparison to reactions with 12C and 4~ projectiles at E/A = 30 MeV a systematics of inclusive fragment production as a function of the projectile mass is obtained. 25.70.Lm; 25.70.Mn; 25.70.Pq to 3.6 GeV, they seem to be associated with the larger IMF multiplicities [ 11 ]. …”
mentioning
confidence: 94%
“…From the comparison to reactions with 12C and 4~ projectiles at E/A = 30 MeV a systematics of inclusive fragment production as a function of the projectile mass is obtained. 25.70.Lm; 25.70.Mn; 25.70.Pq to 3.6 GeV, they seem to be associated with the larger IMF multiplicities [ 11 ]. …”
mentioning
confidence: 94%
“…More recently, inclusive studies of the 3He+" t&g system at energies up to 0556 3.6 GeV have suggested a change in mechanism at bombarding energies in the vicinity of 1.8 GeV total energy [27]. Subsequent coincidence studies [8] with sHe beams have demonstrated the existence of multi&agmentation events for this system. In the present work we examine these latter results in the context of a model in which the energy dissipation stage is described by the intranuclear cascade code (INC) [13] and the decay is described by an expanding, emitting source (EES) undergoing statistical decay [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the production of intermediate mass fragments from the reaction of 600 MeV/nucleon Au incident on a variety of targets has been investigated [8,9]. Production of IMFs has also been examined in reactions of ^He + Ag from 160 to 1200 MeV/nucleon [10,11]. In all these experiments the cross sections of emitted fragments were observed to have a power-law dependence on the charge of the fragment.…”
mentioning
confidence: 98%